Elevated peripheral blood glutamate levels in major depressive disorder - Inoshita M (Dove Medical Press, 2018)
Masatoshi Inoshita,1 Hidehiro Umehara,1 Shin-ya Watanabe,1 Masahito Nakataki,1 Makoto Kinoshita,1 Yukiko Tomioka,1 Atsushi Tajima,2 Shusuke Numata,1 Tetsuro Ohmori1 1Department of Psychiatry, Graduate School of Biomedical Sciences, Tokushima University, Tokushima, Japan; 2Department of Bioinformatics and Genomics, Graduate School of Advanced Preventive Medical Sciences, Kanazawa University, Ishikawa, Japan Purpose: There is growing evidence that glutamatergic signaling may be involved in major depressive disorder (MDD). In regard to peripheral blood glutamate changes in MDD, inconsistent findings have been reported. The purpose of the present study was to evaluate whether blood glutamate levels differed between MDD patients and control participants. Materials and methods: We conducted a systematic review and meta-analysis of 12 association studies between blood glutamate levels and MDD in a total of 529 MDD patients and 590 controls. Subsequently, we conducted subgroup analyses and a meta-regression analysis to examine the sources of potential heterogeneity. Results: A random effects model showed that blood glutamate levels were significantly higher in MDD patients than in controls (standardized mean difference=0.54, 95% CI=0.27–0.82, p=8.5×10-5) with high heterogeneity (I2=75.0%, p<0.05). Subgroup analyses showed elevated glutamate levels in MDD patients compared with controls in plasma, but not serum studies, and in studies using high-performance liquid chromatography but not with mass spectrometry for glutamate assay. A meta-regression analysis showed no effects of age, gender, medication use, sample size, and published year on blood glutamate levels. Conclusion: Our findings suggest that altered glutamate levels may be implicated in MDD, which provides further evidence of glutamatergic dysfunction in MDD. Keywords: glutamate, major depressive disorder, blood, association study, meta-analysis